Coconut-Based Community Economic Development Strategy In Indragiri Hilir Regency - Syarifuddin, Said (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2022)
Indragiri Hilir Regency is an area that has the largest coconut plantation in Indonesia, covering an area of ​​12% of Indonesian coconuts. Most of the ownership belongs to local farmers. This of course will greatly affect the level of the community's economy because about 70% of the people depend on coconut. The purpose of this study is to develop a strategy for the local government to develop a coconut-based community economy, which is expected to be able to overcome fluctuations in coconut prices. The method used in this research is System Literature Review. This method is used to identify, evaluate, and interpret all journal articles and strategies for coconut-based economic development. The results of the study found coconut management strategies and the pattern of developing BUMD and BUMDes through development programs through related OPD and collaborating with companies both local and outside the region in the short term and exporting for the long term.